Characterisation of the contact patch behaviour of an automobile tyre by physical testing. (20th February 2004) - Hall, W.; Mottram, J. T.; Dennehy, D. J.; Jones, R. P.
This paper describes an experimental investigation into the contact patch behaviour of an automobile tyre. The investigation aims to enhance understanding of tyre behaviour in the contact region with reference to the authors' need to validate advanced finite element simulations. Physical tests were carried out with an experimental rolling tyre on flat bed and rolling drum machines, each instrumented with a tri-axial stress transducer. Many plots giving the normal pressure and shear stress distributions under free-rolling and cornering (slip and camber angle) conditions are presented for a high friction surface. A comparison is made between the contact patch behaviour when the tyre is rolled on the horizontal (at 0.18 km/h) and drum (10 to 50 km/h) surfaces. The characteristics of the stress distributions are discussed and related to the actual physical behaviour of the tyre.